The Therapeutic Potential of Adipose Tissue-Derived Mesenchymal Stem Cells to Enhance Radiotherapy Effects on Hepatocellular Carcinoma - Wu, Lingyun; Tang, Qiuying; Yin, Xin; Yan, DanFang; Tang, Mengmeng; Xin, Jiaojiao; Pan, Qiaoling; Ma, Chiyuan; Yan, Senxiang (Frontiers in Cell and Developmental Biology, 2019)
Several studies have investigated strategies to improve the clinical efficacy of radiotherapy (RT) against hepatocellular carcinoma (HCC), yet the prognosis remains poor. Human adipose tissue-derived mesenchymal stem cells (AT-MSCs), easily accessible and abundant in quantity, have represented as an attractive therapeutic tool for the stem cell-based treatment for cancer diseases. Through direct co-culture and indirect separate culture experiments, we showed that AT-MSCs could enhance inhibitory effect of RT on reducing HCC cell growth, migration and invasion in both in vitro and in vivo experiments. RNA-sequencing analysis revealed a noticeable interferon-induced transmembrane 1 (IFITM1) -induced tumor gene signature. Gain and loss of mechanistic studies indicated that mechanism was attributed to downregulated expression of STAT3 and MMPs and upregulated expression of P53 and caspases. Collectively, our findings suggest that AT-MSCs might enhance the therapeutic effects of RT on HCC, providing a rationale for AT-MSCs and RT combination therapy as a new remedy for HCC.